Model Komunikasi di Lembaga Pendidikan Islam - Abdul Malik Karim Amrullah; Zainuddin Fanani (Jurnal Pendidikan Islam Indonesia, 2019)
Communication is a need that is very fundamental for someone in living in a community. Communication and society are two twin words that cannot be separated from each other. Islamic education has meaning as a process of developing and saving human nature. Islamic education does not only develop the body, spirituality, soul and even reason, but how can the four potentials develop and survive. Islamic education institutions are a place, or the place where the process of Islamic education takes place. Islamic education institutions include families, mosques, Islamic boarding schools and madrasas. Institutions that are attached to the soul of Muslims are of two forms, the first form is an institution that cannot be changed and the second form is an institution that can be changed. Islamic education institutions have challenges that must be faced, namely in the fields of politics, culture, science and technology, economics, society and social change, and value systems, and all of them must be neutralized in order to go hand in hand and support each other. Islamic communication models, including human relations with God, human relations with humans, and human relations with themselves. While the communication model in Islamic educational institutions, combines forms of Islamic communication, Islamic communication sources, and basic concepts of Islamic communication.